Programmable Motion-Fault Detection for a Collaborative Robot - Park, Ye Seul; Yoo, Dong Yeon; Lee, Jung Won (IEEE Access, 2021)
Smart factories should be able to respond to catastrophic situations proactively, such as recalls caused by production line disruptions and equipment failures. Therefore, the necessity for predictive maintenance technology, such as fault detection or diagnosis of equipment has increased in recent years. In particular, predicting the faults of collaborative robots is becoming increasingly crucial because smart factories pursue efficient collaboration between humans and devices. However, collaborative robots have the characteristic of executing programmable motions designed by an operator, rather than performing fixed tasks. If existing fault diagnosis methods are applied to non-fixed programmable motions, problems arise in terms of setting absolute criteria for fault analysis, interpreting the meanings of detected values, and fault tracking or fault cause analysis. Therefore, we propose a method of programmable motion-fault detection by analyzing motion residuals to solve the three problems mentioned above. The proposed method can expand the fault diagnostic range of collaborative robots.
Keywords: Collaboration; Collaborative robots; Faults detection; Faults diagnosis; Predictive maintenance; Production line; Programmable motion; Smart factory; Task analysis; collaborative robot; fault diagnosis; predictive maintenance; Programmable motion; smart factory